The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms22116080
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Molecular Mechanisms of Abscisic Acid and Gibberellins Functions in Plants

Abstract: In this special issue entitled, “Advances in the Molecular Mechanisms of Abscisic Acid and Gibberellins Functions in Plants”, eight articles are collected, with five reviews and three original research papers, which broadly cover different topics on the abscisic acid (ABA) field and, to a lesser extent, on gibberellins (GAs) research [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…In this study, AsA and soluble sugar content were shown to accumulate in rice treated with S-ABA under salt stress. Previously, exogenous application of ABA under salt stress significantly increased non-enzymatic defense mechanisms (ascorbic acid (AsA), glutathione (GsH), carotenoids, and flavonoids) in response to oxidative stress [48]. In summary, the results of this study clearly indicate that exogenous S-ABA can effectively alleviate the oxidative damage to rice caused by salt stress by activating multiple defense mechanisms of rice.…”
Section: Exogenous S-aba's Effects On Photosynthetic Efficiency In Ri...mentioning
confidence: 56%
“…In this study, AsA and soluble sugar content were shown to accumulate in rice treated with S-ABA under salt stress. Previously, exogenous application of ABA under salt stress significantly increased non-enzymatic defense mechanisms (ascorbic acid (AsA), glutathione (GsH), carotenoids, and flavonoids) in response to oxidative stress [48]. In summary, the results of this study clearly indicate that exogenous S-ABA can effectively alleviate the oxidative damage to rice caused by salt stress by activating multiple defense mechanisms of rice.…”
Section: Exogenous S-aba's Effects On Photosynthetic Efficiency In Ri...mentioning
confidence: 56%
“…9). Abscisic acid (ABA) inhibits or delays seed germination and embryo development(Yan & Chen, 2017; Quesada, 2021), and it is a positive regulator for seeds responding to dehydration(Smolikova et al ., 2021). This suggests that the inhibition by DNA hyper-methylation might facilitate seed dormancy and make seeds sensitive to dehydration.…”
Section: Discussionmentioning
confidence: 99%